1981
DOI: 10.1029/ja086ia11p09215
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the beam‐plasma discharge

Abstract: It is shown that the scaling observed in a recent experiment of the beam-plasma discharge is consistent with the assumption that triggering occurs when an instability threshold condition is exceeded for electron plasma waves with •0 = •0e, the electron plasma frequency. INTRODUCTIONThe importance of the beam-plasma discharge (BPD) in the feasibility and interpretation of active experiments using electron beams injected in space is very well known [Galeev et al., 1976;Bernstein et al., 1978Bernstein et al., , 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 12 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…An approximate criterion for the ignition of BPD was given before [Rowland et al, 1981' Papadopoulos, 1981 and was found consistent with the observations at the J.S.F.C. tank [Szuszczewicz et al, 1982] as (.De/•"• e > 5.…”
Section: Where K V and Kb Are The Longitudinal Dielectric Functions Osupporting
confidence: 78%
See 2 more Smart Citations
“…An approximate criterion for the ignition of BPD was given before [Rowland et al, 1981' Papadopoulos, 1981 and was found consistent with the observations at the J.S.F.C. tank [Szuszczewicz et al, 1982] as (.De/•"• e > 5.…”
Section: Where K V and Kb Are The Longitudinal Dielectric Functions Osupporting
confidence: 78%
“…Triggering of BPD has been long associated with a beam plasma instability between the electron beam and the beam generated plasma [Kharchenko et al, 1962;Getty and Srnullin, 1963;Galeev et al, 1976Galeev et al, , 1983Linson and Papadopoulos, 1980;Papadopoulos, 1982]. For to, > •r• e and finite size systems Rowland et al [1981] and Papadopoulos [1982], have associated the triggering of the BPD with the threshold for an absolute beam plasma instability near toe' As explained in Papadopoulos [1982] for systems such as the JSC tank the system length (L •< 20 m) is not long enough to allow convective modes to grow to sufficient amplitude. The requirement that the waves grow at frequencies near toe, is connected with the fast rate of nonlinear energy transfer of the beam energy to Copyright 1986 by the American Geophysical Union.…”
Section: C • --•F(p)mentioning
confidence: 99%
See 1 more Smart Citation
“…suggested by Rowland et al [1981] and Papadopoulos [1982]. To aid in the discussion we have plotted the pressure The lifetime of the bursts is less than an ion plasma period ranges in which the observed transitions occurred, against and show little or no spatial collapse.…”
Section: Time Evolution Of the Burstsmentioning
confidence: 99%
“…Since this result and other steady-state BPD signatures are finding what appear to be plausible theoretical descriptions (Rowland et al, 1981 andPapadopoulos, 1981), it is fair to say that the steady-state space-simulated BPD is approaching a reasonable level of accepted scientific understanding. et al, 1979).…”
Section: Manuscript Submitted April 30 1981mentioning
confidence: 99%